The effect of managers on M&As - Dong, Feng; Doukas, John (Journal of Corporate Finance, 2021)
In this paper, we document diverse levels of managerial ability and firm performance in the cross section of acquiring firms. Acquirers with strong managerial ability realize higher announcement-period abnormal returns and experience better post-merger firm performance than their low-ability counterparts. Our results are robust to endogeneity concerns and show that the observed variation in acquirer abnormal returns is attributed to the heterogeneity of managerial ability fixed effects across acquirers. Managerial ability adds value to acquirers, especially in stock-financed acquisitions, implying that the method of payment is not driving the negative stock-financed valuation effect documented in previous literature. Moreover, we find that target firms with strongly ingrained growth potential and low levels of financial constraint and bankruptcy risk are highly favored by skilled acquiring managers.